Nutritional status of 2-5 year old children attending day care centers and those looked after at home in the Medical Officer of Health area, Gampaha - Wijesekara, H.M.A.D.M (My University, 2009)
The study setting was the ECCD centers where both preschools and day care centers are conducted together. Computed sample size for the day care ( DCC) and home care (HC) children were 102 and 210 respectively. As there were only 105 DCC children it was decided to include all of them. Twice the number of DCC children recruited from each centre were selected to the HC group using simple random sampling. A self administered questionnaire was used to collect relevant data and nutritional status of individual child was assessed using standardized techniques. Under nutrition was assessed in terms of underweight, stunting and wasting. The two groups were compared in relevance to the nutritional status and other relevant variables using chi square test. Even though the two groups had significant differences in relation to sociodemographi charactristics, growth monitoring, presence of illnesses with in previous two weeks and food habits none of these factors were found to relate with the under nutritional status of the DCC or HC group. Study revealed that there is no significant difference in nutritional status in day care center cared and home cared, 2-5 year preschoolers in MOH area Gampaha . No significant associations were there in relation to the studied sociodemographic characteristics with the under nutritionsal status of DCC or HC groups. As the studied groups are highly vulnerable for nutritional deficiencies and it affect every aspect of their future life, furture studies on nutrition on this group is very important for the betternment of the future generation.